Correlation between chest CT severity score and C-reactive protein in COVID-19 positive patients admitted in a tertiary care hospital: a retrospective study - Nag, Prathibha; Lakshamanamurthy, Shashibhushan Bangalore; J., Arun B. (International Journal of Research in Medical Sciences, 2022)
Background: COVID-19 has developed into a worldwide pandemic. The early identification of patients who will become severely ill could facilitate the allocation of the limited medical resources to patients in need of aggressive treatment. Aim of the current study was to determine the correlation between COVID-19 severity with inflammatory marker CRP and CT severity score on HRCT thorax Methods: A retrospective observational study was done in 502 hospitalized COVID‑19 patients in a tertiary care hospital BMCRI, Bangalore from August 2021 to September 2021. Clinical and laboratory data of patients were collected. The correlation between clinical severity with chest CT score and CRP were determined by ANOVA test and independent sample t-test was applied among survivors and non survivors. Correlation between CTSS and CRP was analyzed by Pearson correlation analysis. Results: In our present study we found that, out of 502 patients who fulfilled the inclusion criteria 158 patients (31.5%) were triaged as mild cases, 228 patients (45.4%) were moderate case, and 116 patients (23.1%) severe cases. There was statistical significance between CRP values and CTSS among the mild, moderate, severe cases (p<0.001). Both CTSS and CRP values had explicit association with clinical condition of patients. By using independent sample t-test we could derive that CRP and CTSS had strong and significant correlation with the disease severity and mortality. Pearson correlation analysis revealed strong positive correlation between CRP and CTSS in COVID-19 patients. Hence an increase in CRP caused an increase in CTSS with significant p values. Conclusions: In our study we conclude that there is a strong positive clinical correlation between CRP and CTSS in COVID-19 patients reflecting disease severity and mortality.